Viešojo intereso apibrėžimo Lietuvos urbanistinėje plėtroje klausimu - Staniūnas, Eugenijus (Journal of Architecture and Urbanism, 2008)
On definition of public interest in urban development of Lithuania The word “public“ has two meanings in the Lithuanian language. It means “useful for society“ and “overt“ (“nonsecret“). Double-edged meaning of the category is not acceptable in the sphere of practical urban development, where decisions mean the distribution of goods among individuals as well as the distribution of goods among individuals and overall. In general it is not clear whether the development of the city should be only overt or whether it has also something to do with the interest of society, with the interest of the entire population of the city. The language peculiarities require a special approach of the legal system to the term. The Lithuanian legal system makes not very much in this direction, may be rather on the contrary it makes the term “public interest“ even more misty. The Lithuanian Constitution mentions societal interest (requires to support useful for society economic activity), however, neither the Constitution nor the Law on Territory Planning describe what the category “society use“ (societal interest) means. The Law does not see the diference a person and the entirety of city population. It says that the term “public“ (“society“) means one as well as more natural or legal persons. This situation has many sequences: the main question of the social system of the state is not clear; the basis of the mission of urban planning is not clear too; the principle of distribution of goods in urban development is not declared; the question of a legal goods distribution can hardly even be raised. The idea of a more precise legal definition of the term “public interest“ is raised in the paper. The author thinks that the formula “public goods are goods that cannot be produced by an individual“ can be a good basis for elaborating a legal definition of the category “public interest“. It allows to divide clearly and logically overall and individual goods. It allows to see what concrete development proposals are useful for. It allows to show the logical place of urban planning in general: public interest in urban development should be the production of goods that cannot be produced by separate citizens; this production should also be accepted as the mission of urban planning. Article in Lithuanian. Santrauka. Nagrinėjamas viešojo (visuomenės) intereso apibrėžimo ir jo sąsajų su teritorine plėtra klausimas. Apie visuomenės interesus užsiminta Lietuvos Konstitucijoje, tačiau kas tai yra konkrečiau, Lietuvos įstatymuose nepaaiškinta. Neapibrėžus šios kategorijos, praktiškai neįmanoma išspręsti esminio valstybei – jos socialinės sistemos klausimo, t. y. konkretizuoti visuomenės ir individo santykių principo (nors jis apytikriai ir paaiškintas pagrindiniame šalies įstatyme). Rezultatas yra tas, kad gyvenimo praktikoje (taip pat ir teritorinėje plėtroje) realizuojama galbūt nuo Konstitucijos atitrūkusi ir nežinia kokia valstybės idėja. Straipsnyje siūloma šią spragą užpildyti ir analizuojama, kaip tai būtų galima padaryti. Reikšminiai žodžiai: viešasis interesas, visuomenės interesas, apibrėžtumas, įstatymai, urbanistinė plėtra. First Published Online: 22 May 2013